Slip! slide! skate! - Herman, Gail, 1959-; Billin-Frye, Paige (New York, NY : Scholastic Inc, 2003)
A young girl who wants to be the best ice skater in the whole class learns that it is just as important to have fun.
"Cartwheel books."
BR
Keywords: Ice skating -- Fiction; Perfectionism (Personality trait) -- Fiction